The Social Status of Slaves in Rome During the Years (146– 49 BC) - Aso Castro Hassan; Qader Muhamed Hassan (Zanco Journal of Humanity Sciences)
The Roman state is one of the ancient states known in ancient history as the state that included thousands of slaves, especially in the late Republican era due to its many wars and campaigns. In that era, the issue of slaves became a major concern for society and the state alike. This research studied the types of slaves and their social status. Some of them worked in state institutions, lands, farms and homes, and therefore they were exposed to a lot of social injustice as well as oppression and deprivation. In addition, this research also discusses the issue of the social status of slaves in Roman society and the social status of women and children of slaves. On the other hand, the social status of slaves was discussed from the family structure to the various levels of the social structure and their role in this field.